2016
DOI: 10.2147/tcrm.s101346
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interferon gamma on conventional fractionated radiation-induced damage and fibrosis in the pelvic tissue of rabbits

Abstract: We aim to investigate the effect of interferon gamma (IFN-γ) on conventional fractionated radiation–induced damage and fibrosis in ureter and colorectal mucosa. Fifty-two rabbits were randomly divided into three groups comprising a conventional radiation group, an IFN-γ group, and a control group. X-rays were used to irradiate the pelvic tissues of the rabbits in the IFN-γ and conventional radiation groups. Five days after radiation exposure, the rabbits in the IFN-γ group were administered 250,000 U/kg IFN-γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…However, an involvement of VEGF-A can be postulated taking into consideration that VEGF-A is released by bone marrowderived MSCs [Sassoli et al, 2012] and that the role of VEGF-A in inhibiting myofibroblast differentiation, independently, or at least in part independently, from its ability to negatively regulate TGF-β1 signaling, has been demonstrated [Chellini et al, 2018]. On the other hand, other paracrine factors of MSC secretome may negatively interfere with TGF-β1 signaling, synergistically acting as anti-fibrotic agents such as basic fibroblast growth factor, interleukin-15 and interferon-gamma [Sassoli et al, 2012;Yang et al, 2016;Gallego-Muñoz et al, 2017;Manohar et al, 2018]. Moreover, we have recently demonstrated the expression and release of functional MMP-2 by bone marrow MSCs and their autocrine regulation by the sphingosine 1-phosphate (S1P)/S1P receptor axis [Sassoli et al, 2014a[Sassoli et al, , 2018a.…”
Section: Discussionmentioning
confidence: 99%
“…However, an involvement of VEGF-A can be postulated taking into consideration that VEGF-A is released by bone marrowderived MSCs [Sassoli et al, 2012] and that the role of VEGF-A in inhibiting myofibroblast differentiation, independently, or at least in part independently, from its ability to negatively regulate TGF-β1 signaling, has been demonstrated [Chellini et al, 2018]. On the other hand, other paracrine factors of MSC secretome may negatively interfere with TGF-β1 signaling, synergistically acting as anti-fibrotic agents such as basic fibroblast growth factor, interleukin-15 and interferon-gamma [Sassoli et al, 2012;Yang et al, 2016;Gallego-Muñoz et al, 2017;Manohar et al, 2018]. Moreover, we have recently demonstrated the expression and release of functional MMP-2 by bone marrow MSCs and their autocrine regulation by the sphingosine 1-phosphate (S1P)/S1P receptor axis [Sassoli et al, 2014a[Sassoli et al, , 2018a.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies on the effect of IFN‐γ on MFs have been performed in culture and in animal models demonstrating that IFN‐γ may reduce collagen formation during liver and renal fibrosis . In an animal model it was shown that IFN‐γ inhibited the radiation‐induced upregulation of TGF‐β1 mRNA and collagen III protein in the ureter and colorectal mucosa and attenuated radiation‐induced damage and fibrosis . In a rat model of postlaminectomy peridural fibrosis Emmez et al could provide evidence that topical application of low‐dose IFN‐γ is an effective method of preventing peridural fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies on the effect of IFN‐γ on MFs have been performed in culture and in animal models demonstrating that IFN‐γ may reduce collagen formation during liver and renal fibrosis . In an animal model it was shown that IFN‐γ inhibited the radiation‐induced upregulation of transforming growth factor beta (TGF‐β) 1 mRNA and collagen III protein in the ureter and colorectal mucosa and attenuated radiation‐induced damage and fibrosis . In human fibroblastic cell lines Tanaka et al could prove that IFN‐γ blocked the generation of MFs and moderately inhibited the production of α‐SMA in TGFβ1‐promoted MFs indicating that IFN‐γ may be effective in the early stage of contractile diseases to prevent the progression of contractile lesions.…”
mentioning
confidence: 99%